THE CONCEPT OF SOCIAL CAPITAL AND ITS MAIN ELEMENTS (Scientific journal of the Fergana State University, 2025)
This article discusses how social capital has been shaped throughout human history by various natural, historical, socio-economic, political, and spiritual factors. It also addresses the foundation of social capital, which is built on trust, cooperation, mutual assistance, and social relationships among members of society.